Between Law and Narrative : the Method and Function of Abstraction - Lee, Bernon P. (Gorgias Biblical Studies, 2014)
Aside from being the content of speeches by characters in narrative, how do passages of laws in the Pentateuch interact with the surrounding narratives? This book proposes that certain passages of law in Leviticus and Numbers offer direction for the interpretation of adjacent segments of narrative. This 'direction' may serve to emphasize select themes and concepts in narrative. Alternatively, it may misdirect readers, or suggest alternative options to more accessible interpretations for a stretch of narrative.